2017
DOI: 10.31557/apjcc.2017.2.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Surveying Mutation of FLT3 Genes in Children with Acute Leukemia

Abstract: Background and purpose: Mutation of FMS like tyrosine kinase (flt3) gene causes uncontrolled proliferation of leukemic cells and a bad prognosis. The present study is aimed at implementing molecular tests to diagnose and screen the mutations in acute leukemia patients. Methodology: Totally, 91 children with acute myeloid leukemia (AML) and acute lymphoid leukemia (ALL) were examined as to flt3 mutation, internal tandem duplication (ITD) mutation, and point mutation in exon 17 (e17). ITD mutation in flt3 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The cells were then washed with phosphate buffer saline (PBS) containing 2% FCS. Then they were exposed to an Anti-CD4 antibody for 20 minutes at 4°C and finally, these cells were analyzed with a PAS II flow cytometer (Partec GmbH, Munster, Germany) (16). Serum levels of IL-11 and IL-17 were determined by ELISA using ELISA kits protocol (Bender MedSystems GmbH, Vienna, Austria) (17).…”
Section: Cell Count and Serum Level Determinationmentioning
confidence: 99%
“…The cells were then washed with phosphate buffer saline (PBS) containing 2% FCS. Then they were exposed to an Anti-CD4 antibody for 20 minutes at 4°C and finally, these cells were analyzed with a PAS II flow cytometer (Partec GmbH, Munster, Germany) (16). Serum levels of IL-11 and IL-17 were determined by ELISA using ELISA kits protocol (Bender MedSystems GmbH, Vienna, Austria) (17).…”
Section: Cell Count and Serum Level Determinationmentioning
confidence: 99%
“…AML, the most common type of leukemia in adults, is notorious for its heterogeneous genetic characteristics. Numerous molecules and signaling pathways contribute significantly to the molecular pathogenesis of this malignancy (Sheikhi et al, 2017;Giannopoulos, 2019;Stanchina et al, 2020). Currently, targeted therapies are crucial for cancer patients, although strides continue to be made to enhance the efficacy of these treatments and minimize their side effects (Yang and Wang, 2018; RESEARCH ARTICLE Expression and Alteration Value of Long Noncoding RNA AB073614 and FER1L4 in Patients with Acute Myeloid Leukemia (AML) Cucchi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…FLT3 mutations can be divided into two major types: (FLT3-ITD) internal tandem duplication mutations within the juxtamembrane domain (JMD) (involving exon 14 and sometimes part of exon 15), which represents the most common type of FLT3 mutation, found in about 25% of all AML patients, and (FLT3-TKD) point mutations or deletion in the tyrosine kinase domain which affecting codons (835 or 836) occurring in approximately 7-10% of all cases with prognostic value uncertain (Schnittger et al,2012). It was noticed that the occurrence of FLT3-ITD increases with age, where a study indicated that the incidence was lowest in pediatric AML patients and highest in elderly AML patients (Faiz and Rashid, 2019), besides, the mutation was linked to weak emergence and a poor prognosis (Sheikhi et al, 2017). AML patients with FLT-ITD mutation who had a poor prognosis were always with a lower survival rate, indicating that cytogenetic is a crucial prognostic factor in AML (Ait boujmia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%